Customers' adoption of financial services offered by banks and fintechs partnerships: evidence of a transitional economy - Yen H. Hoang; Duong T.T. Nguyen; Linh H.T. Tran; Nhung T.H. Nguyen; Ngoc B. Vu (Data Science in Finance and Economics, 2021)
In recent years, the number of fintech startups has increased substantially, especially those that offer financial services in areas considered as traditional advantage of commercial banks such as payment, deposit or lending services. This paper examines the cooperation in the provision of financial services between banks and Fintech from consumers' perspective, which is the customers' adoption of financial services offered by the partnership between banks and Fintechs. The study employs SEM utilizing data of 234 customers using financial services in Vietnam to identify the factors influence their behaviors and intention to use financial services offered by banks and fintechs partnerships. The findings indicate that perceived usefulness, brand image, user innovativeness and trust have positive effects on customers' attitude and consequently on their intention to use. However, there is no evidence regarding the impact of perceived ease of use and perceived risks on behavior and intention to use of customers. The findings also provide more evidence on the factors that influence the intention of customers' technology acceptance in the traditional Technology Acceptance Model (TAM).